Zambia country brief - Harris, Jody; Drimie, Scott; Roopnaraine, Terry; Park, Seollee; Headey, Derek D.; Covic, Namukolo (Transform Nutrition, 2016)
The Stories of Change research project aims to generate experiential learning for countries with high burdens of malnutrition to start to fill gaps in our understanding of how policies to address nutrition are made and how these policies play out in in implementation in particular contexts. Zambia has come some way over the past years in creating coherent strategies for tackling different aspects of malnutrition; however, important challenges remain.